Global Financial Crisis and Economic Growth: Analysis of The East Asia Economy - Hafeez Hoorani (International Journal of Science and Society, 2020)
In line with the increasingly integrated economy in the midst of globalization, the financial crisis that occurred in one country can easily spread to other countries and become a global financial disaster in a short period of time. In such an event, strong economic fundamentals are essential to defend a country from the effects of a "contagious" crisis. As proof, due to fragile economic fundamentals and a lack of government credibility, the East Asian economy could be attacked easily by the crisis in 1997 once market confidence deteriorated. However, East Asia has learned a lot from the incident in 1997 so that it can prove its resilience in facing the global financial crisis that struck in 2008 by increasing its economic fundamentals and the credibility of policy makers. This paper starts with a theory about economic growth and the financial crisis. Next, empirically examine the extent of the financial crisis in 1997 and 2008 affecting the East Asian economy using econometric panel data. Evidence shows that, although the two crises had a negative impact on the East Asian economy, the 2008 crisis wave was relatively no worse than the 1997 crisis. Finally, this study also provides further explanation of how the East Asian economy has managed to minimize the impact of the global crisis in 2008.